ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEPUASAN PENGGUNA ATM BNI SYARIAH DI BANJARMASIN - HARIYANTO HARIYANTO (At-Taradhi Jurnal Studi Ekonomi, 2013)
The amount obtained from customer satisfaction customer satisfaction score which statesany one customer to several factors: ease of BNI Syariah bank ATM card, ATM card facilities andlocation BNI Syariah BNI bank ATM machines. The research was conducted through primary datacollection with tools questionnaire, given to the customers BNI Syariah Branch ATM usersBanjarmasin. The data obtained is then tabulated to obtain the influence of independent variables onthe dependent variable used. The results and analysis indicate that all the independent variables areused together proven and partially affect customer satisfaction as well as the factors most dominantinfluence customer satisfaction that BNI bank ATM locations.